IMPROVE THE PERFORMANCE OF TECHNOLOGY DIVISION AT PUBLIC ACCOUNTING FIRMS USING LOTUS NOTES R5.5 - Kiki Dewi Pertiwi R; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2004)
Technology division at public accounting firms are responsible for providing facilities and information and communication technology infrastructure for the audit or consultants so they can work wherever they are without experiencing any setbacks. Therefore, this system is designed to document all of the assets division, conduct searches of all activities undertaken by his staff, and to control and manage infrastructure changes that have an impact on the operational processes of the company.